A perturbative approach to the hydrodynamics of heavy ion collisions - Flörchinger, Stefan (Nuclear physics. A, Nuclear and hadronic physics, 2014)
Initial fluctuations in hydrodynamic fields such as energy density or flow velocity give access to understanding initial state and equilibration physics as well as thermodynamic and transport properties. We provide evidence that the fluid dynamic propagation of fluctuations of realistic size can be based on a background-fluctuation splitting and a systematic perturbative expansion in the fluctuating fields. Initial conditions are characterized by a Bessel-Fourier expansion for single events, event-by-event correlations and probability distributions. The evolution equations can be solved order-by-order in the expansion which allows to study the fluid dynamical propagation of single modes, the study of interaction effects between modes, the determination of the associated particle spectra and the generalization of the whole program to event-by-event correlations and distributions.
Gesehen am 24.11.2017